2015
DOI: 10.5812/ijhrba.22702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Psychoactive Substances on Serum Biochemical Parameters

Abstract: Background:Psychoactive substances affect mainly central nervous system and brain function causing changes in behavior.Objectives:The purpose of this study was to determine the effects of different psychoactive substances on serum biochemical parameters.Patients and Methods:The study included 324 drug dependents, and 69 controls. The patient group was determined according to DSM-IV (The diagnostic and statistical manual of mental disorders, fourth edition) criteria. All patients and control subjects were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…Hyponatremia observed in our study may be explained by antidiuretic hormone release triggered by serotonergic pathway activation from sympathomimetic poisoning [ 29 ]. In contrast to our study, Sanli et al [ 28 ] reported a significant increase in serum sodium among studied patients. Hypokalemia observed in some of our patients may also be caused by beta receptor activation associated with sympathomimetic toxicity [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Hyponatremia observed in our study may be explained by antidiuretic hormone release triggered by serotonergic pathway activation from sympathomimetic poisoning [ 29 ]. In contrast to our study, Sanli et al [ 28 ] reported a significant increase in serum sodium among studied patients. Hypokalemia observed in some of our patients may also be caused by beta receptor activation associated with sympathomimetic toxicity [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Hyperglycemia found in the current study may be explained by respiratory depression and ensuing cerebral vasodilatation leading to enhanced glucose entry into the brain [ 27 ]. Conversely, hypoglycemia observed in a small number of our patients is consistent with Sanli et al [ 28 ], who reported that some psychoactive substances may decrease blood glucose levels by suppressing gluconeogenesis, especially among patients with poor nutrition. Hyponatremia observed in our study may be explained by antidiuretic hormone release triggered by serotonergic pathway activation from sympathomimetic poisoning [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most clinical reports imply that opium has no remarkable impact on blood glucose (Table 1 ) whether in non-diabetic (Asgary et al, 2008 ; Roohafza et al, 2013 ; Javadi et al, 2014 ; Masoomi et al, 2015 ; Sanli et al, 2015 ) or in diabetic individuals (Karam et al, 2004 ; Hosseini et al, 2011 ; Rezvanfar et al, 2011 ; Najafi and Sheikhvatan, 2012a ; Bayani et al, 2014 ; Rahimi et al, 2014 ). In some of these studies, glycated hemoglobin (HbA1c), as an indicator of poor control of blood glucose, was significantly higher in addicted groups (Karam et al, 2004 ; Asgary et al, 2008 ).…”
Section: The Impact Of Opium On Blood Glucose and Diabetesmentioning
confidence: 99%
“…There is a disparity regarding the impact of opium on lipid indices in humans (Table 2 ). Several studies on healthy subjects and on individuals who suffered from diabetes mellitus, acute myocardial infarction (AMI) and coronary artery disease (CAD) have indicated no significant relations between opium addiction and triglyceride (TG), total cholesterol (TC), low density lipoprotein (LDL), and high density lipoprotein (HDL) levels (Azod et al, 2008 ; Shirani et al, 2010 ; Najafi and Sheikhvatan, 2012a ; Roohafza et al, 2013 ; Afarinesh et al, 2014 ; Bayani et al, 2014 ; Javadi et al, 2014 ; Masoomi et al, 2015 ; Sanli et al, 2015 ).…”
Section: The Impact Of Opiumonlipid Profile and Dyslipidemiamentioning
confidence: 99%